PROPOSED MARKETING STRATEGY TO CREATE MASS MARKET DEMAND FOR WOODEN FURNITURE BUSINESS LINE OF PT KASEDA SEMESTA JAYA - Corina, Catherine
Promising growth are expected for furniture demand in Indonesia with CAGR of 11.5% up to 2025 through the e-commerce channel, mainly driven by the rising population of middle class income in Indonesia. Moreover, the COVID-19 Pandemic has created the “new normal” where people are working from home, thus new furniture are needed to setup home-office environment. The rising of e-commerce enable people to purchase any size of furniture through their fingertips, and brought threat to the traditional companies, especially companies with B2B market only. In order to survive the digitalization era and grab the market momentum, Kaseda as a B2B wood furniture company will launch its new business line to cater the demand for mass market (B2C). This study will design the new branding strategy for Kaseda’s new business line and explore the suitable marketing channels for Kaseda in order to have the effective communication to its target market using Customer 5A journey, Channel Mapping and benchmarking the existing players in online furniture retailer using Netnography method.